Digital Marketing Communication Strategy In Increasing Cultural Tourism Visitors - Sanusi, Nunung; Susanti, Susan; Triansyah, Fadli Agus (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study examines how marketing communication strategies can influence and increase cultural tourism visitors to Kampung Cireundeu Cimahi. Feedback from the marketing activities carried out, which of these two factors can be done if you can apply the elements in the Digital Marketing Elements such as Product (Product), Price (price), Place (place) Promotion (promotion). This study uses a qualitative method with a descriptive approach. The selection of informants uses purposive sampling, a representative type of data source, namely primary and secondary data. In contrast, data collection techniques are in-depth interviews, observation, and documentation. Data analysis with data reduction, data presentation and conclusion in an integrated manner and significantly, these factors and elements greatly affect the number of tourists visiting Kampung Cireundeu.